2019
DOI: 10.3892/or.2019.6954
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NELL1 on lung cancer stem‑like cell differentiation

Abstract: The cancer stem cell theory recently has received enormous attention in cancer biology. Lung cancer stem-like cells are a subpopulation of undifferentiated lung tumor cells critical for lung cancer tumorigenesis, metastasis and resistance to therapy and disease relapse. The neural EGFL like 1 (NELL1) is a potent growth factor believed to preferentially target cells committed to the osteochondral lineage; yet, its expression and function in lung cancer are largely unknown. In the present study, we used specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Reverse transcription-quantitative (RT-q) PCR. Total RNA was purified using TRIzol ® reagent (Beyotime Institute of Biotechnology) according to a standard protocol (22). The concentration and quality of all the RNA samples were valuated using a NanoDrop 2000 spectrophotometer (Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription-quantitative (RT-q) PCR. Total RNA was purified using TRIzol ® reagent (Beyotime Institute of Biotechnology) according to a standard protocol (22). The concentration and quality of all the RNA samples were valuated using a NanoDrop 2000 spectrophotometer (Thermo Fisher Scientific, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…[72] The neural EGFL like 1 (NELL1) has also been reported to induce differentiation in stem-like cells in lung cancer through inhibiting c-MET-Notch signaling. [73] Wnt signaling pathway is another cascade with the ability to drive both tumor growth and differentiation. The canonical Wnt pathway involves stabilization of free β-catenin which upon translocation into the nucleus drives the transcription of target genes.…”
Section: Signaling Pathways With Dual Rolesmentioning
confidence: 99%
“…[ 72 ] The neural EGFL like 1 (NELL1) has also been reported to induce differentiation in stem‐like cells in lung cancer through inhibiting c‐MET‐Notch signaling. [ 73 ]…”
Section: Signaling Pathways As Potent Targets For Differentiation Therapymentioning
confidence: 99%
“…These associations of Nell-1 expression with tumor tissues make the effects of Nell-1 in tumorigenesis inconclusive. However, Nell-1 increased the chemotherapeutic sensitivity of 95-D lung cancer stem-like cells (Zhai et al 2019), had a negative effect on myoblast invasion (Rapa et al 2012), and inhibited renal cell carcinoma cell migration and adhesion (Nakamura et al 2015). These limited functional studies indicated that Nell-1 may act as a tumor suppressor candidate.…”
Section: Potential Concerns Of Nell-1 For Bone Tissue Engineering Appmentioning
confidence: 99%